2021
DOI: 10.1007/s12020-021-02774-2
|View full text |Cite
|
Sign up to set email alerts
|

LRH-1 high expression in the ovarian granulosa cells of PCOS patients

Abstract: Purpose : Polycystic ovary syndrome (PCOS) is considered as one of the most common endocrine disorder with heterogeneity. There are also reports that liver receptor homolog 1 [LRH-1 or nuclear receptor subfamily 5 group A member 2 (NR5A2)] plays an important role in the reproductive system. But up to now, there are no reports related to the link with PCOS and LRH-1. In this study, we aimed to detect the LRH-1 expression in the ovarian granulosa cell of PCOS patients and explore the potential relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…34 Finally, several studies have investigated the relationship between androgens, such as testosterone, and Lrh-1; however, the exact relationship remains to be elucidated. [35][36][37][38][39] In the current study, no correlation was observed between testosterone levels and midazolam CL. Moreover, a comparison in oral docetaxel pharmacokinetics between patients with mCRPC and newly diagnosed hormonesensitive prostate cancer found no differences between the 2 groups.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…34 Finally, several studies have investigated the relationship between androgens, such as testosterone, and Lrh-1; however, the exact relationship remains to be elucidated. [35][36][37][38][39] In the current study, no correlation was observed between testosterone levels and midazolam CL. Moreover, a comparison in oral docetaxel pharmacokinetics between patients with mCRPC and newly diagnosed hormonesensitive prostate cancer found no differences between the 2 groups.…”
Section: Discussioncontrasting
confidence: 73%
“…Accordingly, Lrh‐1 knockout mice demonstrated increased docetaxel C max and AUC in plasma with lowered hepatic docetaxel concentrations 34 . Finally, several studies have investigated the relationship between androgens, such as testosterone, and Lrh‐1; however, the exact relationship remains to be elucidated 35‐39 . In the current study, no correlation was observed between testosterone levels and midazolam CL.…”
Section: Discussionmentioning
confidence: 50%